2018
DOI: 10.1371/journal.pone.0193615
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine therapy for intracerebral hemorrhage: A systematic review

Abstract: Intracerebral hemorrhage (ICH) is a significant cause of morbidity and mortality worldwide. Several recent controlled trials have reported that deferoxamine (DFX) therapy appears to be effective for ICH. The aim of this study was to perform a systematic review of DFX therapy for ICH patients and evaluate the efficacy and safety of DFX therapy for ICH patients. We searched Medline, Embase, the Cochrane Database of Systematic Reviews, clinicaltrials.gov, all Chinese databases and the reference lists of all inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Various evidence has shown that iron chelators reduce Hb- and iron-induced neurotoxicity attenuates brain edema, and improve functional neurologic outcomes after ICH ( Nakamura et al, 2004 ; Wu et al, 2012 ; Hatakeyama et al, 2013 ). A meta-analysis of 20 studies involving animal models of ICH revealed that DFO was neuroprotective, particularly when administered 2–4 h after ICH induction ( Cui et al, 2015 ), whereas there remains a lack of conclusive clinical evidence regarding iron chelators ( Zeng et al, 2018 ).…”
Section: Potential and Emerging Therapy Targeting Ferroptosis In Acutmentioning
confidence: 99%
“…Various evidence has shown that iron chelators reduce Hb- and iron-induced neurotoxicity attenuates brain edema, and improve functional neurologic outcomes after ICH ( Nakamura et al, 2004 ; Wu et al, 2012 ; Hatakeyama et al, 2013 ). A meta-analysis of 20 studies involving animal models of ICH revealed that DFO was neuroprotective, particularly when administered 2–4 h after ICH induction ( Cui et al, 2015 ), whereas there remains a lack of conclusive clinical evidence regarding iron chelators ( Zeng et al, 2018 ).…”
Section: Potential and Emerging Therapy Targeting Ferroptosis In Acutmentioning
confidence: 99%
“…A systematic review and meta-analysis in experimental models of ICH showed that DFO was neuroprotective, e.g., reduction of brain edema and improvement of neurobehavioral outcomes, especially when it was administered 2-4 h after ICH induction (Cui et al, 2015). In clinical studies, conclusive evidence of the benefit of DFO treatment in ICH (Zeng et al, 2018) or AIS patients is still lacking; some clinical trials of DFO in ICH and AIS are currently ongoing.…”
Section: The Ferroptotic Component Of Stroke-induced Neurodegenerationmentioning
confidence: 99%
“…This finding can be related with the capacity of DFX to cross the BBB and chelate iron ions (Keberle, ), reducing the metal accumulation in the nervous system (Hwang et al., ; Palmer, Roberts, & Bero, ). Thus, through this mechanism, DFX plays a neuroprotective role, and it could be used in the treatment of intracerebral hemorrhage (Selim, ; Zeng et al., ).…”
Section: Discussionmentioning
confidence: 99%